VALUE AND LOVE-BASED LEARNING INNOVATION: EMPIRICAL EVIDENCE OF CHARACTER IMPROVEMENT IN STUDENTS THROUGH DIGITAL LEARNING - Munir, Muhammad; Najib, Muhammad; Islami, Yuliana Nurul; Dariyanto, Dariyanto; Soleh, Muhamad Ibnu; Ayzzaro, Arrinda Luthfiani (LPPM Universitas Jambi, 2026)
This study aims to develop and evaluate the effectiveness of a value- and love-based learning model for enhancing students’ character in digital learning contexts. This study employed a mixed-methods approach with an explanatory sequential design. Quantitative data were collected using pre- and post-tests administered with the Student Empathy and Character Values Scale (SENKS) to measure social empathy, social responsibility, and self-reflection. Meanwhile, qualitative data were obtained through participant observation, interviews, and learning documentation to explore the process of value internalization. The study was conducted over 12 weeks in three Madrasah Ibtidaiyah, involving 90 students in grades V–VI, six teachers, and three principals as key informants. Quantitative data were analyzed using a paired-samples t-test, and qualitative data were analyzed using thematic analysis; the results were integrated to provide a comprehensive understanding. The findings indicate that implementing the value- and love-based learning model significantly improves students’ character holistically. The average character score increased from 68.5 in the pre-test to 83.9 in the post-test (Δ = 15.4; p < 0.001), with the highest improvements observed in social empathy (26.4%), social responsibility (22.6%), and self-reflection (25.4%). Qualitative findings revealed improvements in collaboration (+77.8%), care for peers (+100%), and discipline (+70%), as well as the creation of a supportive classroom climate. The mechanisms of character transformation include emotional awareness, strengthening social relationships through collaboration, and internalizing values through reflection and teacher feedback.